Bulong - Mandap, Margarita Alejandro 1975-; University of the Philippines Diliman College of Mass Communication (Quezon City College of Mass Communication, University of the Philippines Diliman, 2000)
Length:6 minutes; Genre: Narrative; Format: VHS. This video narrative depicts the destruction of family as the safeguard of our species. It show that it is a self-inflicted wound, destroying itself from within by its failure to nurture and value its offspring. It tells the story of a daughter who withdraws herself from her father. She endeavors for recognition of her self-worth through academic excellence but insecurities continue to creep in. Her father emotionally, physically and mentally maligned her and although she did not evolved into a deadly pattern, her personal structure was greatly damaged. Later on when her father was hospitalized, she wished him death instead of healing.
Vita.
Thesis (A.B. Film and Audiovisual Communication)--University of the Philippines Diliman
Keywords: Bulong (Short films -- Philippine).; Family life education -- Philippine